2015
DOI: 10.1186/2049-6958-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Tailored therapy for severe asthma

Abstract: Patients with severe asthma or COPD have often a suboptimal symptom control due to inadequate treatment. A better understanding of pathogenetic mechanisms, phenotypes, endotypes and the new technologies available in the fields of molecular biology and immunogenetics have made it possible to synthesize specific monoclonal antibodies virtually able to interact with any target antigen, or to open a way for new therapeutic target options. At the moment, the only biologic drug available in clinical practice is omal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 60 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…The ongoing EXCELS study (Evaluating Clinical Effectiveness and Long-term Safety in Patients with Moderate-to-Severe Asthma) will shed more information on the natural history of severe asthma and the efficacy of omalizumab [75]. Moreover, there is increasing interest in developing new monoclonal antibodies presenting higher avidity for IgE, such as ligelizumab and lumiliximab, and the ability to interact with low-affinity IgE receptors [76]. Further studies are needed to fully elucidate the exact mechanisms through which anti-IgE treatment benefits patients with severe allergic asthma.…”
Section: Resultsmentioning
confidence: 99%
“…The ongoing EXCELS study (Evaluating Clinical Effectiveness and Long-term Safety in Patients with Moderate-to-Severe Asthma) will shed more information on the natural history of severe asthma and the efficacy of omalizumab [75]. Moreover, there is increasing interest in developing new monoclonal antibodies presenting higher avidity for IgE, such as ligelizumab and lumiliximab, and the ability to interact with low-affinity IgE receptors [76]. Further studies are needed to fully elucidate the exact mechanisms through which anti-IgE treatment benefits patients with severe allergic asthma.…”
Section: Resultsmentioning
confidence: 99%
“…However, asthma is a disease encompassing multiple different phenotypes 11,12 , and cytokines, such as TNF-and TGF-, might also play an important role in certain phenotypes of severe asthma. TNF-is a pleiotropic cytokine that upregulates the expression of adhesion molecules, cytokines, and chemokines in the bronchial mucosa of patients with asthma, implicating an important role for TNF-in the pathogenesis of severe asthma 13,14 . Recent data also showed that TNFinhibits eosinophil apoptosis 15 , and that the TNF-pathway could be associated with airway hyper-responsiveness in obesity, one of the risk factors for the severity of asthma 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these studies, the treatment options for asthma remain limited, and steroids are the predominant type of medication [25]. The discovery of different inflammatory phenotypes in patients with BA and the related molecular phenotyping, thanks to new technologies in the field of molecular biology and immunogenetics, have made it possible to synthesize specific monoclonal antibodies, including anti-cytokine antibodies [26]. Anti-IL monoclonal antibodies should reduce airway inflammation and prevent eosinophilic activation [27].…”
Section: Anti-cytokine Therapymentioning
confidence: 99%